Universities in Crisis? - New Challenges and Strategies in two English City-Regions - Charles, David; Kitagawa, F.; Uyarra, E. (Oxford Journals, 2014)
Universities in the UK have experienced dramatic changes since the onset of the global financial crisis, partly due to the immediate effects of the crisis, but also to the change in national government, upheavals in higher education policy and austerity measures. Increased pressure for local engagement with business has been combined with a rescaling of local economic development governance, and a shift from regional collaboration to a more localist agenda. This paper examines the implications of these changes on university institutional strategies and patterns of collaboration in two city regions: Newcastle and Greater Manchester.